Little author in the big woods : a biography of Laura Ingalls Wilder - McDonough, Yona Zeldis (Christy Ottaviano Books / Henry Holt and Company, 2014)
"Many girls in elementary and middle school fall in love with the Little House books by Laura Ingalls Wilder. What they don't always realize is that Wilder's books are autobiographical. This narrative biography describes more of the details of the young Laura's real life as a young pioneer homesteading with her family on many adventurous journeys. This biography, complete with charming illustrations, points out the differences between the fictional series as well as the many similarities. It's a fascinating story of a much-celebrated writer"--